Analysis of economic value and livestock farming model based on the integration of cattle-palm oil plantation on peatlands in Pasangkayu regency, West Sulawesi, Indonesia - Nazlah K; Aminudin Afandhi; Abdul Haris; Suyadi Suyadi (Faculty of Animal Science, Universitas Brawijaya, 2020)
Pasangkayu Regency is one of the regencies in West Sulawesi that has the potential to apply the concept of sustainable agriculture through palm oil plantations. One of the efforts in developing sustainable farming systems is by integrating agriculture and livestock farming. The purpose of this study is to analyze the economic value and livestock model based on the integration of palm and cattle on peatlands in the Pasangkayu Regency. The study was conducted in palm oil plantations on peatlands in Pedongga District, Pasangkayu Regency from June to August 2018. Data collection techniques were carried out by interviewing and distributing questionnaires directly to 45 informants. The analysis was performed including economic analysis, analysis of sustainability data, analysis of Multiple Goal Programming (MGP), also the drafting of the index and the status of sustainability of integrated palm-cattle. The economic value of the farmers in integrated farming systems of cattle-palm on peatlands in the Pasangkayu Regency showed by the income earned was Rp. 11,069,436.18 / year and much higher than the economic value without integration which the income was only Rp. 916,982.73 / year. The integration-based livestock farming model observed from the ecological, economic, social and cultural, and the legal and institutional dimensions were categorized as sustainable, while the infrastructure and technology dimensions were still below sustainable values. Therefore, the overall integration of palm and cattle on peatlands in the Pasangkayu Regency was categorized as sustainable.